Genome-wide identification of CCD gene family in Peach (Prunus persica L. Batsch) and expression analysis with aroma norisoprenoids - Zhenyu Yao; Wenyi Duan; Ang Li; Wenduo Zhan; Shihang Sun; Lei Pan; Liang Niu; Guochao Cui; Wenfang Zeng (BMC Plant Biology)
Abstract Background Carotenoid cleavage dioxygenases (CCDs) are critical enzymes involved in carotenoid degradation. These enzymes play a significant role in determining fruit color and aroma by modifying carotenoid precursors and generating volatile compounds such as norisoprenoids, volatile carotenoid cleavage products. In peach (Prunus persica), there have been many studies showing that PpCCDs are associated with changes in fruit flesh color, but their role in volatile formation remains to be elucidated. This study aims to explore the function of PpCCD genes in carotenoid metabolism and volatile biosynthesis in peach. Results There were 10 PpCCD genes identified in peach genome. According to the phylogenetic tree, PpCCD proteins were classified into six groups, CCD1, CCD4, CCD7, CCD8, CCD10 and NCED. Analysis of the aroma content revealed that white-fleshed peaches contained significantly higher levels of norisoprenoids than yellow-fleshed peaches, and the expression pattern of PpCCD4 was consistent with this phenotype. The expression pattern of PpCCD4 was correlated with the accumulation of norisoprenoid during fruit development. In addition, MeJA treatment significantly induced the expression of PpCCD4. In addition, subcellular localization studies showed that PpCCD1 and PpNCED2 were localized in the membrane, while PpNCED3 and PpCCD4 were localized in the chloroplast. Conclusion A total of 10 PpCCD genes were identified in peach, among which PpCCD4 was identified as a key gene for the biosynthesis of norisoprenoids. Its expression was higher in white-fleshed peaches and correlated with norisoprenoid levels. PpCCD4 expression was also induced by cold and MeJA treatment, indicating its involvement in stress responses. These findings suggest PpCCD4 is a potential target for improving peach fruit aroma quality.